Effect of blade cap variation on overshot pinwheel performance - Giri Parwatmoko; Dan Mugisidi; Rizki Afif Afandi; Oktarina Heriyani (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
Waterwheels are a medium for producing electrical energy in micro-hydro power plants sourced from waterways that have speed and height. The energy that can be obtained from a waterwheel should depend on the variation of the blades and the placement of the wheel but, the losses caused by wasted water are large. Therefore, this study makes an overshot waterwheel by using blade variations at the top to reduce losses and see the effect of these variations. This study uses 1 wheel with 4 variables: waterwheel without lid (T), waterwheel top blade closed 1/3 (T 1/3), waterwheel top blade closed 1/2 (1/2), and waterwheel top blade closed 2/3 (T2/3). This wheel uses mahogany wood and the blade cap uses acrylic with a thickness of 3mm. The waterwheel was tested using pipes with sizes and flow rates of 1 m3/hour, 2 m3/hour, 3 m3/hour, 4 m3/hour, 5 m3/hour, 6 m3/hour. The efficiency of the capless waterwheel is greater than the closed-blade waterwheel variation. In this study, the 1/3 closed blade waterwheel (T 1/3) is more efficient because the impact losses of the wheel (T 1/3) are lower at 720.13 when compared to the wheel without a lid (T) 1251.90 and the efficiency of the 1/3 closed blade waterwheel (T 1/3) is much higher at 64.38% when compared to the 2/3 closed blade waterwheel (T2/3) at 33.53%. Therefore, the results of this study show that the 1/3 (T 1/3) wheel is more recommended because it has a high enough efficiency and low impact losses.